Proposed subsequent accounting for goodwill: Comparison of IASB and FASB - Yanshan Li; Junsheng Zhang (China Journal of Accounting Studies, 2024)
Since the release and implementation of SFAS No.141 and No.142, there has been a continuous controversy over whether to apply the impairment-only or the amortisation-and-impairment method for subsequent goodwill accounting. FASB and IASB solicited opinions on proposed revisions through the and around 2020, respectively. The comprehensive feedback analysis shows that the number of supportive opinions for amortisation’s comeback is interestingly higher than that for impairment’s retainment. However, it is inappropriate to take the opinions distribution as the sole criteria for standard setting because the preferred methods of the interest groups, based on their stances, mainly stem from their conceptual perceptions of goodwill and the economic consequences of these two methods. This paper provides a theoretical and practical reference for further revision of the standard on the subsequent accounting for goodwill by IASB and FASB.